Pengaruh Influencer Kuliner dan Harga Kompetitif terhadap Minat Beli Mie Gacoan Oleh Generasi Z di Era Digital - Diyas Dimasyara Putri; Dewi Shanti Nugrahani; Adi Sucipto (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2026)
The digital era has positioned culinary influencers and competitive pricing as key determinants of Generation Z’s purchase intention toward viral food products. This study aims to examine the effect of culinary influencers and competitive prices on consumers’ purchase intention for Mie Gacoan in the digital era. This research employed a quantitative explanatory approach with 96 Generation Z respondents selected through purposive sampling. Data collection used a Likert-scale questionnaire and was analyzed using SPSS 26, including multiple linear regression, t-test, F-test, and R². The results show that culinary influencers have a positive and significant effect on purchase intention (β = 0.499; t = 6.674; p < 0.001), as does competitive pricing (β = 0.405; t = 5.419; p < 0.001). Simultaneously, both variables have a significant effect (F = 77.982; p < 0.001) with R² = 0.626, indicating that 62.6% of the variance in purchase intention is explained by these two variables. The implication is that companies should optimize collaborations with credible micro-influencers and maintain competitive pricing strategies to enhance consumer purchase intention.